Analysis of Prospects and Challenges for the Future Development of Hydrogen Vehicles - Yao Zhirong (MATEC Web of Conferences, 2025)
In the context of the global transportation industry, which presently combats environmental pollution and resource scarcity, HPV (hydrogen-powered vehicle) technology stands out as a feasible alternative to electric and ICE (internal combustion engine) vehicles. The current article aims to present a review of the benefits that relate to the usage of HPVs, including FCEVs and HICEs, with the focus on efficiency, emissions, and range. The essay also delves into the current limitations of the existing power sources, emphasizing the factors of technology, economy, and society as the main obstacles to hydrogen adoption. This assessment includes a comprehensive study of hydrogen storage, transportation, infrastructure, production, and public perception. Strategies are designed that could enable transportation with hydrogen to become more feasible. The results indicate that, given the current circumstances, HPVs seem not to be in a position for mass adoption. However, both innovative technologies and policy support can serve as important necessary prerequisites to placing HPVs as one of the pillars for sustainable future transportation.